2020
DOI: 10.35314/inovbiz.v8i2.1627
|View full text |Cite
|
Sign up to set email alerts
|

Green Human Resource Management dan Kinerja Lingkungan: Studi Kasus pada Rumah Sakit di Kota Palembang

Abstract: Based on the Environmental Quality Index reported by the Ministry of Environment and Forestry of the Republic of Indonesia, in 2017 the Environmental Quality Index rank of South Sumatra slipped to rank 20 nationally, wherein the previous year was ranked 16. Environmental performance was one of the factors in Environmental Quality Index. Most of the previous research on environmental performance and GHRM was carried out in the manufacturing industry analysis units, while other industrial fields have not been st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
0
5
0
2
Order By: Relevance
“…Furthermore, [31] indicated that if companies do not include their workers in ecological activity, they will affect their ecological success. However, [34] noted later that many companies now rely very actively on protecting their community by their workers.…”
Section: Green Human Resource Management and Environmental Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, [31] indicated that if companies do not include their workers in ecological activity, they will affect their ecological success. However, [34] noted later that many companies now rely very actively on protecting their community by their workers.…”
Section: Green Human Resource Management and Environmental Performancementioning
confidence: 99%
“…This would help companies hit their environmental sustainability goal. Moreover, [34] green training and advancement are often deemed an essential human resources strategy for organizational success in environmental performance. Environmental training is considered an essential method for developing human resources [33,35].…”
Section: Green Human Resource Management and Environmental Performancementioning
confidence: 99%
“…Teknik dokumentasi adalah yang paling sering digunakan untuk mengumpulkan data penelitian yakni pada 48 penelitian. Sedangkan penelitian yang menggunakan kuesioner hanya 2 penelitian, yakni yang dilakukan oleh Hadjri et al (2020) dan Renaldo et al (2022). Gambar 6.…”
Section: Instrumen Penelitianunclassified
“…The current reality of GSI reflects planning to protect the organizational environment and asking organizational leaders to pay more attention to organizational activities to enable employees to play an active role in providing services to minimize environmental pollution in the workplace (Lin & Chen, 2018). According to Hadjri et al (2020); Chen et al (2015); Khammadee and Ninaroon (2022); Lin and Chen (2018), researchers have looked at the performance of GSI, and several studies have revealed that GSI could significantly improve SOP.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%